Physiological adaptation and spectral annotation of Arsenic and Cadmium heavy metal-resistant and susceptible strain Pseudomonas taiwanensis. (August 2019) - Satapute, Praveen; Paidi, Murali Krishna; Kurjogi, Mahantesh; Jogaiah, Sudisha
Abstract: In the present study, the 16S-rRNA sequencing of heavy metal-resistant and susceptible bacterial strains isolated from the industrial and agriculture soil showed resemblance with Pseudomonas taiwanensis . Based on the growth rate, two bacterial strains SJPS_KUD54 and KUD-MBBT4 exhibited 10 ppm tolerance to Arsenic and Cadmium. These two heavy metals caused, a significant increase in stress enzymes like superoxide dismutase, catalase and glutathione S-transferase activities in SJPS_KUD54 when compared to KUD-MBBT4. Following heavy metal treatment, the atomic-force-microscopy observations showed no change in the cell-wall of SJPS_KUD54, whereas the cell-wall of KUD-MBBT4 got ruptured. Moreover, the protein-profile of SJPS_KUD54 treated with heavy metals exhibited varied patterns in comparison with untreated control. In addition, the accumulation of hydroxyl, thiol and amides were found in the SJPS_KUD54 relative to its control. Furthermore, the resistant SJPS_KUD54 strain showed a remarkable bioaccumulation properties to both Arsenic and Cadmium. Thus, it is inferred that the growth rate, stress enzymes and functional-groups play a significant role in the physiological-adaption of SJPS_KUD54 during stress conditions, which is positively involved in the prevention or repair mechanism for reducing the risks caused by heavy metal stress. Graphical abstract: Image 1 Highlights: Bacterium possessing bioabsorption of heavy metals was isolated. The impact of heavy metals on microbial growth and enzyme activities was studied. SJPS_KUD54 strain exhibited physiological adaption to stress conditions. IR functional group confirms the resistant strain SJPS_KUD54 to metal tolerance. Resistant strain can be utilized for bioremediation of heavy metals and waste management.